2017
DOI: 10.1111/jbi.12991
|View full text |Cite
|
Sign up to set email alerts
|

Did interaction between human pressure and Little Ice Age drive biological turnover in New Zealand?

Abstract: Aim To test for simultaneous Holocene biogeographic turnover events in the New Zealand region. Specifically, we synthesize ancient DNA, radiocarbon data and archaeological data to assess the chronologies of late Holocene lineage extinction and replacement. Location Cool‐temperate coastal ecosystems of New Zealand and the subantarctic. Methods We present new ancient DNA and radiocarbon data for New Zealand sea lions, and synthesize existing climatic, genetic and archaeological data, to test for synchronous mega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…The extinct lineages were subsequently replaced by Australian C. atratus ( figure 3). This newly characterized 'turnover' event highlights that extinction can potentially facilitate major phylogeographic shifts, and parallels similar extinction-colonization events in costal and marine megafauna [25][26][27]29,32]. Anthropogenic impact and predation by introduced mammals no doubt caused the rapid extinction of C. sumnerensis-indeed, the presence of Cygnus remains in archaeological midden deposits attests to their use as food [24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The extinct lineages were subsequently replaced by Australian C. atratus ( figure 3). This newly characterized 'turnover' event highlights that extinction can potentially facilitate major phylogeographic shifts, and parallels similar extinction-colonization events in costal and marine megafauna [25][26][27]29,32]. Anthropogenic impact and predation by introduced mammals no doubt caused the rapid extinction of C. sumnerensis-indeed, the presence of Cygnus remains in archaeological midden deposits attests to their use as food [24].…”
Section: Discussionmentioning
confidence: 85%
“…New Zealand's rich archaeological record [24] presents intriguing opportunities to unravel the often complex dynamics between human populations and indigenous wildlife [25][26][27][28][29][30][31]. Recent analyses of ancient DNA (aDNA) have led to paradigmatic shifts in our understanding of the evolution of NZ's biota [32]. In particular, genetic studies of prehistoric remains have revealed a number of 'cryptic' biological turnover events, highlighting the role of density-dependent processes constraining lineage distributions [33] and leading to reappraisals of which lineages are truly 'native' [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the importance of disturbance in facilitating such structure (e.g. lineages expanding from remnant patches: Davies, Cary, Landguth, Lindenmayer, & Banks, 2016), or by allowing opportunistic lineage turnover (Waters, Fraser, Maxwell, & Rawlence, 2017) has only recently begun to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Many New Zealand plants and animals, once considered ancient, have been shown to be more recent transoceanic immigrants arriving long after the separation of Zealandia from eastern Gondwana (e.g., Knapp et al, 2005;Mitchell et al, 2014). The oceans surrounding the New Zealand archipelago are a permeable barrier (e.g., McCulloch et al, 2017) and, while the focus has been on species mobility, establishment and persistence of immigrants is just as important (Boessenkool et al, 2009;Collins et al, 2014;Rawlence et al, 2015Rawlence et al, , 2017aGrosser et al, 2016;Waters and Grosser, 2016;Waters et al, 2017).…”
Section: Introductionmentioning
confidence: 99%